Knowledge Gaps Update to the 2019 IPCC Special Report on the Ocean and Cryosphere: Prospects to Refine Coastal Flood Hazard Assessments and Adaptation Strategies With At-Risk Communities of Alaska - Williams, Dee M.; Erikson, Li H. (Frontiers in Climate, 2021)
This article reviews the status of ongoing knowledge gaps and co-production process challenges that still impede coastal flood hazard resilience planning in communities of northwestern Alaska where threat levels are high. Discussion focuses on the state of knowledge arising subsequent to preparation of the 2019 IPCC Special Report on the Ocean and Cryosphere in a Changing Climate, and highlights prospects to address urgent needs. The intent is to identify some key steps necessary to advance the integration of relevant multidisciplinary observations with flood modeling and infrastructure mapping to co-produce new online hazard and risk assessment tools that inform local community planning and improve science collaboration among Federal, state, and regional partners for enhanced pre-storm preparations and post-storm recovery, including partial or complete relocation. By focusing coastal data integration for delivery of priority geospatial hazard map products through a consistent yet customized approach to adaptation planning, the broad collaborative effort in Alaska may yield a path of stakeholder service delivery that can be applied to many Arctic communities and other vulnerable regions of the world. Additionally, advancement of resilience planning in Alaska may indirectly help establish a stronger and more persistent national alignment with Arctic interests and identity.